Mechanical Sensorless Speed Control of Permanent Magnet Motors Driving an Unknown Load - de Angelo, Cristian Hernan (2006)
A new sensorless scheme for high-performance speed control of permanent-magnet ac motors (PMACMs) driving an unknown load is proposed. This scheme uses an extended nonlinear reduced-order observer to estimate the induced electromotive force (EMF) and load torque. From the estimated variables, the rotor position, the rotor speed, and the position derivative of flux are calculated and are used to close the control loop. In order to improve the drive performance, the estimated load torque is incorporated as a feedforward signal in the closed control loop. In addition, the proposed sensorless PMACM drive allows the torque-ripple and copper-loss minimization for motors with an arbitrary EMF waveform. Simulation and experimental results to validate the proposal are presented in this paper.